East German unemployment: the myth of the irrelevant labor market - Christian Merkl; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2008)
This paper indicates that East Germany's unemployment originates primarily in the labor market, caused by the fast wage adjustment after German reunification. We model the resulting labor market traps in a search and matching framework, show that they are difficult to overcome, and provide empirical evidence. We argue that under these circumstances, demand-side policies are effective mainly when they increase the economy's overall productivity and thereby help overcome the labor market traps.
Keywords: E24; J30; J64; P2; 330; Unemployment; labor market trap; East Germany; Arbeitslosigkeit; Lohnpolitik; Anspruchslohn; Nationale Einheit; Rationalisierung; Arbeitsproduktivität; Arbeitsmarktflexibilisierung; Neue Bundesländer